The Future of Employment – Between the Equilibrium Price of Labor and the Equilibrium Working Time in Actual and / or Potential Production - Sotirova, Maria (Research Papers, 2020)
The new industrial age changes the nature of labor comprehensively - both as a human activity and as a factor of production with its market mechanisms of distribution and use. The purpose of the study is to reveal the impact of technological modernization on labor use and its impact on the effective functioning of the labor market. In this sense, the research task is focused on finding the optimal compromise between the effective and full use of labor potential, combining the impact of the cost of labor as an element of the market mechanism and working time as an institutional norm. The methodological approach of the research is based on the analysis and evaluation of the contemporary processes and trends that change the strength of the relationship between economic growth and employment. The main estimates and conclusions are that economic growth no longer generates employment at previously known scales and proportions. Therefore, the research interest is aimed at disclosure of the potential of working time as an institutional tool for influencing employment levels, but with efficient use of labor and functioning of the labor market at full employment rate. Attempts have been made to formalize dependencies and develop simulation models revealing the impact of both variables (labor cost and working hours) on employment numbers in actual and potential production. At this stage, the study is limited to justifying the theoretical consistency of the dependencies and the possibilities for modeling them under different combinations of variables. The proposed research approach and method can be used to justifying or evaluation the impact of options on public (regulatory and investment) labor market policies.
Keywords: Employment; Working hours; Economic growth; Labor market